2012
DOI: 10.1080/02701367.2012.10599821
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of School-Day Physical Activity in Preschool Students

Abstract: This study examined the relationship among sex, body mass index, motor skill competence (MSC), perceived physical competence (PPC), and school-day physical activity in preschool students (N = 34). Physical activity was assessed by steps accumulated during the school day, while MSC and PPC were assessed with the Test of Gross Motor Development-2nd edition (Ulrich, 2000) and the Pictorial Scale of Perceived Competence and Social Acceptance (Harter & Pike, 1984). Regression analyses revealed that preschool studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
80
2
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 31 publications
4
80
2
6
Order By: Relevance
“…20,38 The strength of the current study is the sufficient number of randomly selected preschools ensuring power and heterogeneity for studying important potential correlates while avoiding the use of arbitrarycut points forcategorizingvariables. Furthermore, the PA measurements were simultaneously carried out in the preschools over the course of a few weeks, reducing season and weather effect.…”
Section: Discussionmentioning
confidence: 99%
“…20,38 The strength of the current study is the sufficient number of randomly selected preschools ensuring power and heterogeneity for studying important potential correlates while avoiding the use of arbitrarycut points forcategorizingvariables. Furthermore, the PA measurements were simultaneously carried out in the preschools over the course of a few weeks, reducing season and weather effect.…”
Section: Discussionmentioning
confidence: 99%
“…7 Many schools in New York City low-income communities (eg, Bronx, NY) do not even have gymnasiums, school playgrounds, or PE teachers. 8 Although there are few published studies of pedometer-determined PA during the school day in US children, [9][10][11][12] current data suggest PA is low in resource-poor communities. 12 In a review, Tudor-Locke et al used 3 studies to establish a range of average number of pedometerdetermined steps for boys and girls during a school day: 6700 to 7600 steps for boys and 4900 to 6100 steps for girls.…”
mentioning
confidence: 96%
“…Five studies used multiple objective methods of measuring physical activity and sedentary behaviour (Van Cauwneberghe et al, 2012;Pagels et al, 2011;Dowda et al, 2009;Trost et al, 2003;McKenzie et al, 1992), for example OSRAP as well as accelerometers (Trost et al, 2003). Of the 27 studies included, most (74%) reported moderate-to vigorous-intensity physical activity (MVPA) (Pate et al, 2014;Stephens et al, 2014;Vanderloo et al, 2014;Olesen et al, 2013;Shen et al, 2013;Vanderloo et al, 2013;Raustorp et al, 2012;Van Cauwenberghe et al, 2012;Nicaise et al, 2011;Pagels et al, 2011;Sugiyama et al, 2011;Dowda et al, 2009;Grontved et al, 2009;Bower et al, 2008;Pate et al, 2008;Williams et al, 2008;Dowda et al, 2004;Pate et al, 2004;Trost et al, 2003;McKenzie et al, 1992), and many (56%) reported total physical activity (TPA) (Pate et al, 2014;Vanderloo et al, 2014;Gagne & Harnois, 2013;Vanderloo et al, 2013;Gubbels et al, 2012;Robinson et al, 2012;Gubbels et al, 2011;Pagels et al, 2011;Bower et al, 2008;Cardon et al, 2008;Pate et al, 2008;Boldemann et al, 2006;Trost et al, 2003;McKenzie et al, 1992). Sedentary behavior was reported in thirteen studies (48%) …”
Section: Summarising the Articlesmentioning
confidence: 99%
“…More than half the studies (56%) were conducted in the U.S. (n=15) (Pate et al, 2014;Stephens et al, 2014;Byun et al, 2013;Shen et al, 2013;Raustorp et al, 2012;Robinson et al, 2012;Nicaise et al, 2011;Dowda et al, 2009;Williams et al,. 2008;Pate et al, 2008;Bower et al, 2008;Dowda et al, 2004;Pate et al, 2004;Trost et al, 2003;McKenzie et al, 1992), with the remaining conducted in Canada (n=3) (Vanderloo et al, 2014;Vanderloo et al, 2013;Gagne & Harnois, 2013), Sweden (n=3) (Raustorp et al, 2012;Pagels et al, 2011;Boldemann et al, 2006;), Netherlands (n=2) (Gubbels et al, 2012;Gubbels et al, 2011), Belgium (n=2) (Van Cauwenberghe et al, 2012;Cardon et al, 2008), Denmark (n=2) (Olesen et al, 2013;Grontved et al, 2009), and Australia (n=1) (Sugiyama et al, 2011).…”
Section: Summarising the Articlesmentioning
confidence: 99%
See 1 more Smart Citation